The Use of Literature in Teaching English to Enhance EFL Students’ Writing Skill - Firman, Muhammad (English Education Department STKIP Agama Hindu Singaraja, 2022)
Literature like short stories, novels, poems, and songs can contain many values in teaching English specially in writing skill. The present study focuses on the use of literature in teaching English to enhance EFL students’ writing skill. By employing descriptive method, it is revealed that literature can enhance EFL students’ writing skill in many aspects such as grammar, vocabulary, and punctuation. These results were revealed directly through EFL students’ perspectives and indirectly through author’s description during the observation. From these findings, it can be concluded that the use of literature in teaching English are beneficial and efficient in enhancing EFL students’ writing skill. Observation, open-ended questionnaire, and interview, literature in teaching English were classified as media in teaching English, topic in teaching English, and activity in teaching English. The present study concludes that the use of literature in teaching English are important to enhance EFL students’ writing skill.